(untitled) - Pagana, Kathleen Deska (St. Louis, Mo., 2005)
Mosby’s diagnostic and laboratory test reference provides the user with an up-to-date, essential reference that allows easy access to clinically relevant laboratory and diagnostic tests. A unique feature of this handbook is its consistent format, which allows for quick reference without sacrificing the depth,...
Keywords: Diagnosis, Laboratory,Laboratory Techniques and Procedures,Nursing Care